Impact of Social Identity on Women Entrepreneurial Intention/ Behavior: Mediating Role of Attitude Towards Behavior and Moderating Role of Personal Network - Jamila Khurshid; Jamila Khurshid; Nabila Khurshid; Muhammad Ishfaq Khan (Elementary Education Online, 2023)
In this study, researcher incorporates the concept of social identity into entrepreneurship and analysis whether social identity of the women impact on their decision to become an entrepreneur and socialized theiror not.This cross-sectional study was conducted through research questionnaire survey by adopting valid instruments. To this tenacity, the relevant data collected from 895 respondents ‘those were female students. The reliability test applied preceded by Pearson correlation test for significant association among variables. The hierarchical regression analysis (bootstrap) applied to test the impact of factors on women entrepreneurial intentions that leads to their behavior using SPSS- 20. The result showed that women with social identity scored higher on women entrepreneurialintention. As a moderator personal network positively influence on women entrepreneurial intention. Moreover, results suggest significant direct and indirect effects of social identity through the mediating variable, attitudes towards behavior and dependent variable women entrepreneurial intention. The findings of this study will contributeto the corporate body of knowledge and be useful to regulators and policy makers to encourage and enhance the business intention of women, enabling them to contribute their expected role in Pakistan